IMPLEMENTASI KEBIJAKAN DISIPLIN APARATUR SIPIL NEGARA DI BADAN KEPEGAWAIAN DAERAH KABUPATEN PARIGI MOUTONG - Harmin, Harmin (Katalogis, 2018)
Discipline Apparatus Civil State In Agency Staffing District Parigi Moutong have not been implemented optimally. The purpose of this research is knowing how the Implementation Policy Discipline Apparatus Civil State at the Agency Staffing District Parigi Moutong. Types of research used qualitative and selection informants techniques is purposively with 5 selected informants. Data collected through interviews, observation and documentation. Data analysis techniques through the stages of data reduction, data display, draw conclusions and verification. The theory used is the model of implementation of the policy of George C. Edwards III with 4 aspects of communication, resources, disposition andÂ  bureaucratic structures. The results showed that the Implementation Policy Discipline Apparatus Civil State In Agency Staffing District Parigi Moutong not been implemented optimally dueÂ  to the aspect of communication, of resources, disposition and bureaucratic structure has not gone well because of less optimal time coaching, education is still minimal, information is slow and indecision of leadership led to less support policy the implementation of the Policy Discipline Apparatus Civil State In Agency Staffing District Parigi Moutong. Â